Pengaruh Struktur Modal, Likuiditas, Pertumbuhan Laba Dan Ukuran Perusahaan Terhadap Kualitas Laba Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI 2019-2021 - Gunawan Aji; Nur Fidia; Vina Nur Azizah; Aisyah Amini (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to determine the effect of capital structure, liquidity, profit growth, and company size on earnings quality in mining sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Earnings Quality Variables using Quality of Income. The sample method used was purposive sampling. From the population in the Mining Sector Companies during the 2019- 2021 period, 13 companies that met the sample criteria were taken. The analytical tool used is multiple linear regression analysis. Data processing in this study used the SPSS (Statistic Package for the Social Sciens) software program 25.00 for Windows. The results showed that capital structure, profit growth, and company size had no negative and insignificant effects on earnings quality. Liquidity has a positive and significant effect on earnings quality. The influence of Capital Structure, Liquidity, Profit Growth, and Company Size together has a positive and significant effect on earnings quality in mining sector companies listed on the IDX.